Real-world effectiveness and safety of eculizumab in AQP4-IgG-positive neuromyelitis optica spectrum disorder - Koc, Emine Rabia; Yetkin, Mehmet Fatih; Saridas, Furkan; Turan, Omer Faruk; Sevim, Serhan; Terzi, Murat; Siva, Aksel (Springer Heidelberg, 2026)
ObjectiveTo evaluate the real-world effectiveness and safety of eculizumab in patients with AQP4-IgG-positive neuromyelitis optica spectrum disorder (NMOSD) and to identify predictors of disability outcomes.MethodsThis multinational, retrospective cohort study analyzed data from 46 patients across 26 centers. The outcomes included the annualized relapse rate (ARR), relapse-free status, change in expanded disability status scale (EDSS) scores, and adverse events. To identify predictors of EDSS improvement or worsening, patients were stratified into subgroups (improved vs. stable/worsened) at each follow-up time point and compared based on demographic, clinical, and radiological variables.ResultsThis retrospective cohort study included 46 patients with AQP4-IgG-positive NMOSD from 26 centers, followed for a mean of 27.3 months. The mean ARR significantly decreased from 1.1 in the 2 years pre-treatment to 0.1 during eculizumab therapy. The relapse-free rate increased from 6.5% pre-treatment to 80.4%. Mean EDSS scores improved from 4.2 at baseline to 3.6 at 24 months. The presence of area postrema syndrome was associated with a favorable prognosis, while the presence of spinal attacks was associated with a poor prognosis at 12 months. Adverse events occurred in 7 patients (18.9%), leading to permanent discontinuation in only two.ConclusionEculizumab demonstrated robust real-world effectiveness in reducing relapse rates and stabilizing disability, with an acceptable safety profile. Clinical outcomes may be influenced by attack phenotype, underscoring the importance of early intervention.
Keywords: Neuromyelitis optica spectrum disorder; Eculizumab; Real-world study